Integrating Andragogy and Project-Based Learning to Enhance Life Skills Competency Among Adult Learners - Azizah, Zahratul; Solfema, Solfema; Darmansyah, Darmansyah; Angraini, Ezi; Biru, Rembulan Catra Banyu (Universitas Negeri Padang, 2025)
This research the integration of andragogy and project-based learning (PjBL) to enhance life skills competency among adult learners in a fashion training program at LKP Anggrek Padang, Indonesia. Despite the potential of PjBL to foster practical and cognitive skills, its effectiveness in informal adult education remains limited when disconnected from adult-centered learning principles. Using descriptive qualitative methods—participant observation, interviews with 12 learners and one instructor, and document analysis—this study examines how instructional practices align with Malcolm Knowles’ andragogical principles. Findings show that while PjBL engaged learners in collaborative garment-making projects, teaching remained teacher-centered, with rigid instructions and external evaluations. Learner autonomy, experiential reflection, and intrinsic motivation were underemphasized, resulting in missed opportunities to develop critical life skills such as problem-solving, self-direction, and adaptability. The misalignment between adult learners’ characteristics and pedagogical approach highlights a gap in instructor understanding of andragogy. The study concludes that effective life skills development requires more than PjBL implementation—it demands intentional integration with andragogical foundations. Recommendations include andragogy-based teacher training and curriculum redesign for vocational programs targeting adults.